2011
DOI: 10.1200/jco.2010.32.4939
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction of Nonprogression in Advanced Non–Small-Cell Lung Cancer Treated With Erlotinib By Using [18F]Fluorodeoxyglucose and [18F]Fluorothymidine Positron Emission Tomography

Abstract: Early FDG-PET predicts PFS, OS, and nonprogression after 6 weeks of therapy with erlotinib in unselected, previously untreated patients with advanced NSCLC independent from EGFR mutational status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
135
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(147 citation statements)
references
References 21 publications
10
135
1
1
Order By: Relevance
“…Patients with lower early and late residual tumor glycolysis ( 18 F-FDG uptake) and proliferation ( 18 F-FLT uptake) had a significantly prolonged progression-free survival. In another study of 34 patients, the changes in 18 F-FDG and 18 F-FLT uptake after 1 and 6 wk of erlotinib treatment were compared with nonprogression measured by CT after 6 wk of treatment (74). Early 18 F-FLT response predicted longer progression-free survival (hazard ratio, 0.31; 95% confidence interval, 0.10-0.95; P 5 0.04) but not overall survival and could not predict nonprogression after 6 wk of therapy.…”
Section: Lung Cancermentioning
confidence: 99%
“…Patients with lower early and late residual tumor glycolysis ( 18 F-FDG uptake) and proliferation ( 18 F-FLT uptake) had a significantly prolonged progression-free survival. In another study of 34 patients, the changes in 18 F-FDG and 18 F-FLT uptake after 1 and 6 wk of erlotinib treatment were compared with nonprogression measured by CT after 6 wk of treatment (74). Early 18 F-FLT response predicted longer progression-free survival (hazard ratio, 0.31; 95% confidence interval, 0.10-0.95; P 5 0.04) but not overall survival and could not predict nonprogression after 6 wk of therapy.…”
Section: Lung Cancermentioning
confidence: 99%
“…They also found that an infiltrative "radiographic signature" predicted a worse prognosis [6]. Zander et al [16] and Sohn et al [17] found that FDG and Fluorothymidine (FLT), respectively, early in the course of treatment could predict outcomes to EGFR-TKI treatment. Additional authors have explored radiolabelled nuclear techniques of direct imaging of EGFR expression [18,19].…”
mentioning
confidence: 99%
“…Conceptually it may represent the most metabolically active part of the tumour, which might contain the most prognostic or predictive value. Zander et al [6] showed that use of SUV max is a suitable predictive parameter and that it performed equally well compared to other SUVs. Moreover SUV max is uniquely defined, i.e.…”
mentioning
confidence: 99%
“…In addition to diagnosis and staging, FDG PET/CT is used to measure treatment response. Here residual FDG uptake or changes in uptake during or after treatment are used as predictive factors [4][5][6]. To this end, criteria to measure FDG uptake changes and/or metabolic response have been proposed [7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation